CUSTOMER LOYALTY: IMPROVE CUSTOMER RELATIONSHIP MANAGEMENT THAT IMPACT THE CUSTOMER SATISFACTION - Muang, Muh. Shadri Kahar; Setiawan, Edi Indra; Masati, Rikal Fajar (Al-Amwal : Journal of Islamic Economic Law, 2021)
This study aims to determine theÂ effect ofÂ customer relationship management consisting of people, processes, on customer satisfaction and loyaltyÂ in Palopo CityÂ .Â This study uses a quantitative research approach byÂ examining specific populations or samples, sampling techniques are generally carried out randomly, collecting data using research instruments, statistical data analysis with the aim of testing hypotheses that have been setÂ usingÂ Smart PLSÂ 3.2.8Â softwareÂ .Â The results showed that theÂ customer relationship managementÂ variableÂ which consists of people, processes, and technology has a positive and significant impact on customer satisfaction.Â Customer relationship managementÂ consisting of people, processes, and technology has a positive and significant influence on customer loyalty, while satisfaction has a positive but not significant effect on customer loyalty.Â The indirect effectÂ (mediation)Â shows that satisfaction can mediate the influence ofÂ customer relationship managementÂ consisting of people, processes, and technology on customer loyalty.